Revitalisasi Pos Baca Sebagai Upaya Mewujudkan Budaya Literasi Bagi Masyarakat Kelurahan Bandulan Kota Malang - Richo Surya Pradana; Jefrianus Nakut (Sevaka : Hasil Kegiatan Layanan Masyarakat, 2024)
The aim of this service activity is to improve the community's ability to manage reading parks and create a culture of literacy in the community, especially early childhood. The implementation of this revitalization program involved a service team consisting of 20 students in collaboration with Karang Taruna in RT 04/RW 02, Bandulan Village, which had 25 members. Implementation of community service activities is carried out in four stages, including: (1) Location survey stage, the service team has received a recommendation from the sub-district regarding the existence of a reading post which has been neglected for a long time, approximately 3 years; (2) In the planning stage, the service team prepares plans starting from cleaning the reading post, followed by replacing the tiered iron shelves for bookshelves, painting the reading post, making wall shelves for folding tables, sorting and adding to the book collection at the reading post, adding inventory in the form of stationery, blackboards, wall clocks, fans, folding tables, trash cans and doormats; (3) In the implementation phase there are several activities, including: a) Cleaning the reading post; b) Painting reading posts; c) Installation of bookshelves and arrangement of inventory and book collections; d) Manufacture and installation of wall shelves; e) Carpet installation; f) Implementation of tutoring; g) Socialization of reading post management. The enthusiasm of the community and Karang Taruna who attended the socialization that had been carried out, so that the reading post could function again after a 3 year hiatus.